2D analytical model for surface potential based electric field and impact of wok function in DMG SB MOSFET. (September 2017) - Kumar, Prashanth; Bhowmick, Brinda
Abstract: In this paper an analytical surface potential model of a dual material gate (DMG) Schottky Barrier (SB) metal-oxide-semiconductor field effect transistor (MOSFET) is explored. The surface potential model is established by using two-dimensional solution of Poisson's equation, with essential boundary conditions near the drain and source ends. The proposed device has metal-semiconductor (Schottky) junction instead of p-n junction. In the DMG structure the effect of work function, drain to source voltage, gate to source voltage on the surface potential are observed. Furthermore, the simulation results of proposed DMG-SB-MOSFET shows good immunity to short channel effects(SCE) and is assessed by considering the drain-induced barrier lowering(DIBL) and compared with equivalent single material gate (SMG) SB- MOSFET. Moreover, the DMG and SMG SB-MOSFET are compared in terms of ambipolar behavior, ON-state and OFF-state current of the device. The developed analytical model for surface potential along the channel length are in close agreement with the Silvaco Technology Computer Aided Design device simulator data. Highlights: The analytical model is based on the solution of 2D Poisson's equation in the channel for proposed DMG SB MOSFET. Channel lengths, different work function of gate material have been optimized to minimize the SCE of the device. Suppressing of ambipolar leakage using DMG Schottky MOSFET. The improved Ioff is stated hence increased Ion /Ioff ratio is obtained.